EKF- and UKF-Based Estimators for Radar System - Singh, U. K.; Singh, A. K.; Bhatia, V.; Mishra, A. K. (Frontiers in Signal Processing, 2021)
In radar, the measurements (like the range and radial velocity) are determined from the time-delay and Doppler shift. Since the time-delay and Doppler shift are estimated from the phase of the received echo, the concerned estimation problem is nonlinear. Consequently, the conventional estimator based on fast Fourier transform (FFT), is prone to yield high estimation errors. Recently nonlinear estimators based on kernel least mean square (KLMS) are introduced and found to outperform the conventional estimator. However, estimators based on KLMS are susceptible to incorrect choice of various system parameters. Thus, to mitigate the limitation of existing estimators, in this paper, two efficient low-complexity nonlinear estimators; namely, the extended Kalman filter (EKF) and the unscented Kalman filter (UKF) are proposed. The EKF is advantageous due to its implementation simplicity; however, it suffers from the poor representation of the nonlinear functions by the first-order linearization. Whereas, UKF outperforms the EKF and offers better stability due to exact consideration of the system nonlinearity. Simulation results reveal improved accuracy achieved by the proposed EKF and UKF based estimators